2020
DOI: 10.1155/2020/3750294
|View full text |Cite
|
Sign up to set email alerts
|

MCMs in Cancer: Prognostic Potential and Mechanisms

Abstract: Enabling replicative immortality and uncontrolled cell cycle are hallmarks of cancer cells. Minichromosome maintenance proteins (MCMs) exhibit helicase activity in replication initiation and play vital roles in controlling replication times within a cell cycle. Overexpressed MCMs are detected in various cancerous tissues and cancer cell lines. Previous studies have proposed MCMs as promising proliferation markers in cancers, while the prognostic values remain controversial and the underlying mechanisms remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 95 publications
3
56
0
Order By: Relevance
“…Given that these targeted drugs are non-specific, they affect the entire replication process of normal and tumor cells leading to concomitant death [ 45 ]. Prevailing evidence indicates that MCM family proteins act as helicases in the initial stage of DNA replication, and are key regulators of cell cycle checkpoints [ 46 ]. For instance, MCM2-7 complexes contribute to the initiation of cell cycle, and are therefore potential markers for tumor screening and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Given that these targeted drugs are non-specific, they affect the entire replication process of normal and tumor cells leading to concomitant death [ 45 ]. Prevailing evidence indicates that MCM family proteins act as helicases in the initial stage of DNA replication, and are key regulators of cell cycle checkpoints [ 46 ]. For instance, MCM2-7 complexes contribute to the initiation of cell cycle, and are therefore potential markers for tumor screening and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, the aberrant expression of MCM family members has been reported in a wide range of cancers, and cancer cell malignant phenotypes can be suppressed by knockdown of these genes [ 31 , 32 , 33 , 34 ]. Our recent study showed that siRNA-mediated knockdown of MCM4 attenuated the aggressiveness of lung adenocarcinoma cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 Recent studies have suggested that dysregulated MCMs lead to tumor initiation, progression, and chemoresistance via modulating cell cycle and DNA replication stress. 23 , 24 Overexpressed MCMs are detected in various cancer tissues and are potential biomarkers for the diagnosis and prognosis of many kinds of cancers. Wu et al 25 found that high levels of MCM2 were observed in LUSC and associated with adverse tumor features.…”
Section: Discussionmentioning
confidence: 99%